2015
DOI: 10.1002/cjce.22358
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of polyethylene/TiO2 nanocomposites using a vanadium catalyst

Abstract: In this study, a vanadium (III) complex bearing a salicylaldiminato ligand of the general formula [RN=CH(2,4‐tBu2C6H2O)]VCl2(THF)2, where R = 2,6‐iPr2C6H3, was used as a catalyst. Titanium dioxide doped with iron nanofillers was synthesized by a sol‐gel process and used to investigate the effect of nanofillers on ethylene homopolymer and ethylene/propylene copolymer properties. To the best of our knowledge, this is the first time titanium dioxide doped with iron has been used as a nanofiller in ethylene polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…[47] The study of incorporating iron-doped TiO 2 filler on the synthesis and properties of polyethylene and ethylene/ propylene copolymer nanocomposites using a vanadium catalyst revealed that sol-gel-based iron doped TiO 2 filler strongly affected catalytic performance, polymer molecular weight and molecular weight distribution, crystallinity and composition of copolymer, and thermal properties of homo-(polyethylene) and co-polymer (polyethylene/polypropylene) nanocomposites. [51] For homo-polymer nanocomposites, the activity has a linear relationship with filler content varying from 5 to 15 mg. The chain propagation was largely responsible for the increase in activity with increase in filler content.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…[47] The study of incorporating iron-doped TiO 2 filler on the synthesis and properties of polyethylene and ethylene/ propylene copolymer nanocomposites using a vanadium catalyst revealed that sol-gel-based iron doped TiO 2 filler strongly affected catalytic performance, polymer molecular weight and molecular weight distribution, crystallinity and composition of copolymer, and thermal properties of homo-(polyethylene) and co-polymer (polyethylene/polypropylene) nanocomposites. [51] For homo-polymer nanocomposites, the activity has a linear relationship with filler content varying from 5 to 15 mg. The chain propagation was largely responsible for the increase in activity with increase in filler content.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%